Job Satisfaction and Citizenship Behavior of Employees of Private Universities in the Central Jakarta Region - Suryani, Rahayu Endang; Herminda, Herminda; Darmin, Darmin (International Review of Management and Marketing, 2019)
The purpose of this research is to know and analyze job satisfaction factors and citizenship behavior of employees private university. The methods of this research are descriptive and causality methods. Problems of this research formulated in 7 hypotheses that SEM tests analysis with Lisrel 8.80 software and 214 respondents. The research finding is there is the positive and significances influence of the Organizational commitment and work-life balance simultaneously on job satisfaction, and there is the positive and significances influence of the Organization commitment, work-life balance, and job satisfaction simultaneously on behavior of organizational citizenship, wherever job satisfaction is the dominant variable to more influence on behavior of organizational citizenship. Advice managerial, to build behavior of organizational citizenship employees, in the future, management private university have to build job satisfaction through the working conditions of that supports. While to improve job satisfaction, management private university have to build Affective commitment and work-life balance trough Personal Life Enhancement of Work employees private university in Central Jakarta. Keywords: organizational commitment, work-life balance, job satisfaction, organizational citizenship behavior. JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7682